EFFORTS TO OVERCOME CRIMINAL ACTS OF SKIMMING COMMITTED THROUGH ATMS IN THE PERSPECTIVE OF LAW NUMBER 19 OF 2016 CONCERNING EIT - Putu Eka Trisna Dewi; Ni Made Septiwidiantari (NOTARIIL Jurnal Kenotariatan, 2021)
Cybercrime is one form of the negative impact of the development of science and technology. One of the crimes in the form of Cybercrime, which in recent years has greatly disturbed the public, is skimming. Skimming crimes continue to increase and are unsettling the community. For this reason, serious efforts to overcome them are required. This study aims to examine the effort to overcome criminal acts of skimming committed through ATMs in the Perspective of Law Number 19 of 2016 concerning EIT. This study is legal research with a literature study. The research approaches used are the statute approach and the fact-based approach. The results of this study revealed that as an effort to tackle skimming crime, there are two ways that can be applied, namely preventive action (preventing crime from occurring) and repressive action (efforts taken after a crime has occurred). The repressive measures that can be taken in tackling the crime of skimming are to apply legal provisions in accordance with Article 30 in conjunction with Article 46 of Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning EIT.